An Intelligent Wall Painting and Spraying System - Mahakud, JJ; Pattanaik, Priyabrata (International Journal of Psychosocial Rehabilitation, 2025)
Wall painting is a dreary, debilitating and risky procedure which makes it a perfect case for mechanization. The painting had been computerized in the car industry but not for the construction business. There is a solid requirement for a versatile robot that can move to paint inside walls of private structures. In this paper, the calculated structure of a self-sufficient wall painting robot is portrayed comprising of an arm that sweeps the walls vertically and is fitted on a versatile robot base to give the parallel feed movement to cover the work of art region. The objective is to fulfil the criteria of straightforwardness, low weight, easy and quick painting time. The sensors are embodied on the arm and the portable base to modify as far as possible and move in the room territory. A control framework is intended to direct the arm movement and plan the versatile base movement. This paper introduces a procedure for building up a paint robot, which is fit for performing paintwork on an inside wall. This technique combines highlights, for example, identification of the surface harshness, paint consistency, paint thickness forecast, and complex structure designs printing on the wall.